2023
DOI: 10.3390/ijms242015122
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of GH3 Gene Family in Potato and Functional Characterization of StGH3.3 under Drought Stress

Panfeng Yao,
Chunli Zhang,
Tianyuan Qin
et al.

Abstract: As an important hormone response gene, Gretchen Hagen 3 (GH3) maintains hormonal homeostasis by conjugating excess auxin with amino acids during plant stress-related signaling pathways. GH3 genes have been characterized in many plant species, but they are rarely reported in potato. Here, 19 StGH3 genes were isolated and characterized. Phylogenetic analysis indicated that StGH3s were divided into two categories (group I and group III). Analyses of gene structure and motif composition showed that the members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…GH3 enzymes add amino acid residues to free IAA molecules, forming conjugates that reduce the pool of active auxin available for signaling. Numerous studies have demonstrated that under drought stress conditions, the expression of these genes is upregulated ( Yuan et al., 2013 ; Feng et al., 2015 ; Singh et al., 2015 ; Yao et al., 2023 ). For instance, in Arabidopsis, an activation-tagged wes1-D dwarf mutant exhibits a 44.6% reduction in free IAA levels, accompanied by a 621% increase in IAA-Asp conjugates under abiotic stress.…”
Section: Auxin In Plantsmentioning
confidence: 99%
“…GH3 enzymes add amino acid residues to free IAA molecules, forming conjugates that reduce the pool of active auxin available for signaling. Numerous studies have demonstrated that under drought stress conditions, the expression of these genes is upregulated ( Yuan et al., 2013 ; Feng et al., 2015 ; Singh et al., 2015 ; Yao et al., 2023 ). For instance, in Arabidopsis, an activation-tagged wes1-D dwarf mutant exhibits a 44.6% reduction in free IAA levels, accompanied by a 621% increase in IAA-Asp conjugates under abiotic stress.…”
Section: Auxin In Plantsmentioning
confidence: 99%